Pemanfaatan Tata Ruang Di Daerah Aliran Sungai Citarum Kabupaten Karawang - Pohan, Rizka Handayani; Irawan, Gustira Sabrina; Ramadhani, Rima Vania; Saputra , Fernando (PT. Sharia Journal and Education Center, 2024)
ABSTRACT Land use control is an effort to create an orderly spatial arrangement. Given the limited space and the increasing public awareness of the importance of spatial planning, there is a need for transparent, effective methods that involve public participation to create spaces that are safe, comfortable, productive, and sustainable. Changes in spatial planning and land use are factors that can directly affect ecosystems and the services they provide (M.A. Board, 2001). In the Citarum River Basin, changes in land use impact river flow, sediment transport, and the presence of dissolved substances. The degradation of the Citarum River Basin is caused by the conversion of protected areas into development zones. Additionally, changes in land use also result in alterations to land cover, where areas with vegetation have better water absorption capacity compared to developed residential areas. The ecosystem in the upper part of the river basin plays a crucial role in protecting the entire basin in terms of water management. Any changes in land use in the upper basin can affect the entire river basin and disrupt the balance of the water management system. Kata Kunci: Spatial Planning, Utilization, Citarum Watershed ABSTRAK Pengendalian pemanfaatan ruang merupakan upaya untuk menciptakan penataan ruang yang teratur. Dengan keterbatasan ruang dan meningkatnya kesadaran masyarakat akan pentingnya penataan ruang, diperlukan metode yang transparan, efektif, dan melibatkan partisipasi publik untuk menciptakan ruang yang aman, nyaman, produktif, dan berkelanjutan. Perubahan tata ruang dan penggunaan lahan adalah faktor yang dapat secara langsung mempengaruhi ekosistem serta layanan yang dihasilkannya (M.A. Board, 2001). Di Daerah Aliran Sungai (DAS) Citarum, perubahan dalam penggunaan lahan berdampak pada perubahan aliran sungai, pengangkutan sedimen, dan zat terlarut lainnya. Degradasi DAS Citarum terjadi akibat alih fungsi lahan dari kawasan lindung menjadi kawasan pengembangan. Selain itu, perubahan penggunaan lahan juga mengakibatkan perubahan tutupan lahan, di mana area yang ditumbuhi tanaman memiliki kemampuan serap air yang lebih baik dibandingkan dengan daerah yang telah dibangun untuk perumahan. Ekosistem di bagian hulu DAS berperan penting dalam melindungi keseluruhan DAS dalam hal pengelolaan air. Setiap perubahan dalam penggunaan lahan di bagian hulu DAS dapat memengaruhi seluruh DAS dan mengganggu keseimbangan sistem tata air. Kata Kunci: Tata Ruang, Pemanfaatan, DAS Citarum